Does Ownership Structure Influence Firm Value? An Empirical Research towards the Bucharest Stock Exchange Listed Companies - Vintila, Georgeta; Gherghina, Stefan Cristian (International Journal of Economics and Financial Issues, 2015)
The aim of this study is to research the influence of ownership structure on firm value in order to provide, from our knowledge, the first results for the case of the Bucharest Stock Exchange listed companies. Therefore, we have considered the shareholdings of the following types of shareholders: insiders, companies from financial intermediation sector, State, and employees’ organizations, over the period 2007-2011. Thus, after the econometric estimations using panel data regression models, we have concluded a negative influence of insider shareholdings and employees’ organizations ownership on firm value. However, the results showed a lack of association between State shareholdings and firm value. There resulted a nonlinear relationship between the shareholdings of the companies from financial intermediation sector and firm value. Furthermore, the impact of ownership structure, one year lagged, on contemporaneous firm value was the same, although the magnitude of the influence was higher. Keywords: corporate governance; ownership structure; firm value; Romania; panel data models JEL Classifications: G32; G34